Strategi Pengendalian Sampah Plastik Guna Mendukung Kelestarian Hidup Di Kota Semarang Ditinjau Dari Perwal No. 27 Tahun 2019 tentang Pengendalian Penggunaan Plastik - Pratiwi, Farida Hesti; Islami, Dianita Nurul; Rajib, Rayi Kharisma (Jurnal Ilmiah Wahana Pendidikan, 2024)
Plastic waste is one of the pressing environmental problems in Indonesia, including in the city of Semarang. This article analyzes plastic waste control strategies in Semarang City to support environmental sustainability and evaluates their effectiveness in supporting environmental sustainability. The purpose of writing this article is to analyze plastic waste control strategies in the city of Semarang with the aim of supporting environmental sustainability, while also evaluating the effectiveness of plastic waste control in supporting environmental sustainability in the city. The research method used is normative juridical with a descriptive analytical literature approach. The results of the analysis show that the City of Semarang has implemented various plastic waste control strategies, including communication in policy, resource allocation, disposition, and bureaucratic structure. However, policy implementation is still faced with challenges, such as a lack of public understanding and a lack of resources. This article concludes that efforts to control plastic waste require synergy between the government, community and business actors to achieve success in preserving the environment in Semarang City.